Institutions and entrepreneurship: Unidirectional or bidirectional causality? - Ali Hussein Samadi (Journal of Global Entrepreneurship Research, 2019)
There are various studies on the role of institutional and non-institutional factors in developing the level and nature (or types) of entrepreneurship. In these studies, there have been no attention to the causal relationship between these variables, and the direction of the causality are considered unidirectional and from institutions to the entrepreneurship. Furthermore, the current studies have only investigated the role of institutional factors in developing entrepreneurship for the short-run and there was no attention for a long-run. Moreover, it should be noted that, this relationship is studied disregarding the level of the economic development of countries. Therefore, the main aim of this article is to investigate the causality between institutions and entrepreneurship regarding to the level of economic development (Factor-driven, Efficiency-driven and Innovation-driven countries) in both short and long term. The results show that the bidirectional causality between institutions and entrepreneurship is confirmed only in the innovation-driven countries, and only in the long-run.
Keywords: K42; K00; 650; Institutions; Entrepreneurship; Causality; Development level; Short-run; Long-run